Investigation of fatigue behavior of Kevlar composites with nano-Graphene filled epoxy resin. (2022) - Singh, D.; Vijaya Dharshan, G.N.; Akshay, A.; Kumar, R.R.; Gaur, P.; Ganesan, C.; Jensin Joshua, J.; Nisha, M.S.
Abstract: The fatigue behaviour of Kevlar based fibre-reinforced composites is often less studied and requires further investigation. The objective of this study is to investigate the fatigue behaviour of the Kevlar composites reinforced epoxy infused with Graphene nanoparticles. Most of the engineering components used in defense, aerospace, biomedical, automobile industries and military appliance use aramid fiber as primary structural component. The Kevlar has low compressive strength and other cons there by limiting its mechanical and electrical behavior in various applications. In this study, kevlar-49 and graphene nanoparticle infused epoxy are sandwiched together using vacuum resin infusion technique. The difference in visual appearance of Graphene, Graphite and Carbon Nanotubes often leads to misconception; hence to visualize the graphene nanoparticle in a non-destructive format, the Raman Spectroscopy was performed. The fatigue test was then conducted at constant stress amplitude having an R ratio of 0.2 with frequency of 10 Hz, in accordance to ASTM D3479. The fatigue limit was observed at 1, 005, 498 million cycles. The visual view of the fatigue experiment illustrates the damage propagation of the developed composites which is started by matrix cracking followed by fiber breakage and delamination between Kevlar fiber layers once the developed composite reaches the failure point. Thus, this development of Nanoparticle reinforced composite shows good agreement findings and has high potential to replace or reduce the usage of general synthetic fibers.